SUATU TINJAUAN TERHADAP PERATURAN MENGENAI PENCABUTAN PERMOHONAN KASASI DALAM PENYELESAIAN PERKARA PERDATA - Herman Herman (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTION  This study aims to review of legislation governing the time limit for filing the petition cassation an learn about the process and procedures for revocation request in the resolution of civil cases Cassation. As is well known, if the parties are litigating civil felt  dissatisfied with a decision of the High Court does not accept the ruling, then he can apply Cassation, the Supreme Court as stipulated in Law no.4 of 2004 on the Supreme Court. As for the right to nominate Cassation is the litigants themselves, because it was he who acts as the material, which is directly involved in the conflict were sued. The results showed that when the cassation has exceeded the time limit of 14 days, then it can not be accepted back, while the day in requestion, including weekdays and does not include holiday or official grand and revocation of cassation by the applicant, in principle, allowed for his case yet decided by the Supreme Court, in case of revocation of the applicant’s appeal of his case in the Supreme Court examination not be performed or stopped.However, if only one party who revoke cassation, where as the other parties who filed an appeal does not withdraw the application, then the examination of the case on appleal is still being done.In this case the lifting of cassation should be set firmly and clearly and clearly in the National Civil Procedures Law to come, so it does not harm either party